The Effect of Competency, Compensation and Work Discipline on Employee Performance in Service Division PT. United Motors Center Suzuki Surabaya - Azmi Facriyah; Yulyar Kartika Wijayanti (Universitas Dinamika, 2021)
The purpose of this study is to determine whether competence, compensation and work discipline partially and simultaneously affect employee performance in PT. United Motors Centre Suzuki Ahmad Eigis Surabaya. Types research is explanatory research with quantitative analysis. The sample population is employees in the service division totaling 46 employees. Data collection techniques using survey with questionnaire as instrument. The data analysis technique used multiple linear regression, t-test aand F-test to test the hypothesis with the SPSS program. The resuls of this study shows that competence, compensation and diciplines as partially and simultaniously significant effect on employee performance, and the effect of competence on employee performance is the most significant among the other three variables. Its indicate that increasing performance of employees can be determined by competence, compensation and work discipline of employees at division service PT. United Motors Centre Suzuki Ahmad Yani Surabaya.